2013
DOI: 10.1111/acem.12149
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance Use Is Associated With Higher Self‐rated Illness Seriousness: User Attitudes and Perceptions

Abstract: Objectives: The objective was to study the role and effect of patients' perceptions on reasons for using ambulance services in Queensland, Australia.Methods: A cross-sectional survey was conducted of patients (n = 911) presenting via ambulance or selftransport at eight public hospital emergency departments (EDs). The survey included perceived illness severity, attitudes toward ambulance, and reasons for using ambulance. A theoretical framework was developed to inform this study.Results: Ambulance users had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
(35 reference statements)
0
26
0
Order By: Relevance
“…Transportation issues, for example, not having a car, prompted some service users to choose the ED, ambulance, or urgent care services rather than primary care and this was identified by three studies 58, 60, 64. One study reported that 34% of patients chose to use the ambulance service instead of primary care due to not having a car 64.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation issues, for example, not having a car, prompted some service users to choose the ED, ambulance, or urgent care services rather than primary care and this was identified by three studies 58, 60, 64. One study reported that 34% of patients chose to use the ambulance service instead of primary care due to not having a car 64.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 34% of patients chose to use the ambulance service instead of primary care due to not having a car 64. However, for some population groups there were barriers to using out‐of‐hours and ED services and this affected their choice of service.…”
Section: Resultsmentioning
confidence: 99%
“…Growth of ambulance use is increasing in the United States (US) and other industrialized nations [1][2][3][4][5][6]. Adult patients with high rates of ambulance utilization, especially for low acuity complaints, are disproportionately uninsured or have public insurance [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Survey data by Mooney et al suggest that many patients chose not to call EMS primarily because they believed that it was not needed, or that they could get to the hospital faster using other forms of transportation. Toloo et al found that a general sample of EMS users cited a variety of reasons for the decision to call an ambulance, including belief that care would be expedited once arriving in the ED, lack of a personal vehicle, and a perception that its use would not constitute a misuse of resources. Other studies point to perception of illness, severity of symptoms, and presence of comorbidities as determinants of EMS use .…”
Section: Introductionmentioning
confidence: 99%
“…Toloo et al found that a general sample of EMS users cited a variety of reasons for the decision to call an ambulance, including belief that care would be expedited once arriving in the ED, lack of a personal vehicle, and a perception that its use would not constitute a misuse of resources. Other studies point to perception of illness, severity of symptoms, and presence of comorbidities as determinants of EMS use . Our study sought to identify patient‐reported factors for STEMI patients' decisions to use EMS in our region.…”
Section: Introductionmentioning
confidence: 99%